2021
DOI: 10.7717/peerj.10706
|View full text |Cite
|
Sign up to set email alerts
|

Myofascial release versus Mulligan sustained natural apophyseal glides’ immediate and short-term effects on pain, function, and mobility in non-specific low back pain

Abstract: Background Myofascial release (MFR) and Mulligan Sustained Natural Apophyseal Glides (SNAGs) are manual therapy techniques routinely practiced in the management of non-specific low back pain (NSLBP). As a solo intervention or along with other therapies, both methods have reported positive results for individuals with NSLBP. However, which technique improves NSLBP-related pain, restricted range of motion (ROM) and disability, warrants further research. Obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The results of this study are in accordance with the study done by Bhat et al They saw the effects of spinal mobilization in lumber radiculopathy and results were in accordance with our study. There was significant improvement in pain with p-value <0.05 14 .…”
Section: Discussionmentioning
confidence: 88%
“…The results of this study are in accordance with the study done by Bhat et al They saw the effects of spinal mobilization in lumber radiculopathy and results were in accordance with our study. There was significant improvement in pain with p-value <0.05 14 .…”
Section: Discussionmentioning
confidence: 88%
“…Another study by Bhat et al (2021) showed a consistent result that using MFR therapy on lumbar to sacroiliac muscles with strengthening exercise enabled them to reduce pain and physical disability among patients with LBP. Boff et al (2021) reported the combination of spinal manipulation and MFR has yielded a similar effect in pain intensity and disability compared to the spine manipulation group post-3-week intervention and at follow-up.…”
Section: Level Of Pain and Disabilitymentioning
confidence: 78%
“…Some studies use MFR alone compared to sham MFR (Arguisuelas et al, 2017), or the electrotherapy modalities (Tamartash & Bahrpeyma, 2022). Previous studies evaluated the effects of MFR on the back and lower limb muscles (Arguiselas et al, 2017;Balasubramaniam et al, 2014;Branchini et al, 2015); combined MFR with manual therapy (Ajimsha et al, 2014) or physical modality (Arun 2014) or active exercises (Ajimsha et al, 2014;Bhat et al, 2021;Yu et al, 2016).…”
Section: Single Versus Combination Myofascial Release Therapy With Pa...mentioning
confidence: 99%
See 1 more Smart Citation
“…Manual therapy is a specialized area in physiotherapy which manages neuromuscular pain. Manual therapy techniques include the Maitland mobilization technique, Kaltenborn mobilization technique, Mulligan technique [6], active release technique, and many more. Manual therapy mainly works on arthrokinematics and osteokinematics of the joint.…”
Section: Introductionmentioning
confidence: 99%